2006
DOI: 10.1128/jb.00072-06
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Insights into Metabolic Adaptations inAlcanivorax borkumensisInduced by Alkane Utilization

Abstract: Alcanivorax borkumensis is a ubiquitous marine petroleum oil-degrading bacterium with an unusual physiology specialized for alkane metabolism. This "hydrocarbonoclastic" bacterium degrades an exceptionally broad range of alkane hydrocarbons but few other substrates. The proteomic analysis presented here reveals metabolic features of the hydrocarbonoclastic lifestyle. Specifically, hexadecane-grown and pyruvate-grown cells differed in the expression of 97 cytoplasmic and membrane-associated proteins whose genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 50 publications
6
144
0
1
Order By: Relevance
“…Since the cultivation of Alcanivorax borkumensis [88], functional genomic, biochemical and physiological analyses have revealed the underlying basis of its success [52,[89][90][91]. While it lacks catabolic versatility, utilising alkanes almost exclusively as carbon and energy sources, it has multiple alkane-catabolism pathways, with key enzymes including alkane hydoxylases (a non-haem diiron monooxygenase; AlkB1 and AlkB2) and three cytochrome P450-dependent alkane monooxygenases [89].…”
Section: Marine Ecosystemmentioning
confidence: 99%
“…Since the cultivation of Alcanivorax borkumensis [88], functional genomic, biochemical and physiological analyses have revealed the underlying basis of its success [52,[89][90][91]. While it lacks catabolic versatility, utilising alkanes almost exclusively as carbon and energy sources, it has multiple alkane-catabolism pathways, with key enzymes including alkane hydoxylases (a non-haem diiron monooxygenase; AlkB1 and AlkB2) and three cytochrome P450-dependent alkane monooxygenases [89].…”
Section: Marine Ecosystemmentioning
confidence: 99%
“…Varying levels of light intensity iTRAQ and LC-M/MS [43] Heterotrophy/photoautotrophy 2-D PAGE, MALDI-MS and LC-MS/MS [50] Nutrient availability/different C-and energy sources [68,74,75] Growth phase/cell cycle…”
Section: Proteome Signatures In Response To Changing Environmental Comentioning
confidence: 99%
“…While A. borkumensis is hardly detectable in clean water, it can be one of the most abundant microorganisms found in oil-polluted waters [72,73]. Details of alkane degradation pathways used by A. borkumensis could recently be elucidated in a comprehensive proteomic study [74]. Comparing protein patterns from cells grown on pyruvate and hexadecane, respectively, a number of cytoplasmic as well as many membrane-associated proteins could be identified that are specifically induced during growth on alkanes.…”
Section: Highly Specialized Marine Bacteriamentioning
confidence: 99%
“…For instance, AlkB-like monooxygenase typically oxidizes liquid alkanes but, lately, few members of this family of enzymes were described to be also induced by propane [66,67]. This underlines the diversity that can exist the proteomic analysis of its cytoplasmic and membrane proteins after the growth on nhexadecane showed the presence of multiple alkane hydroxylase systems belonging to different families [75] involved in the primary oxidation of a broad range of alkanes.A review of the molecular genetics and regulations of the categories of bacterial monooxygenases involved in the n-alkanes metabolism reported in literature is summarized below. …”
mentioning
confidence: 98%
“…The expression of both alkB1 and alkB2 is very low when cells grow using pyruvate as the carbon source, but is strongly induced when C 10 -C 16 alkanes are metabolized; expression decreases considerably upon entry into stationary phase [70,75,213]. A gene coding for a protein showing similarity to the P. …”
Section: Differential Regulation Of Multiple Alkane Hydroxylasesmentioning
confidence: 99%